2020
DOI: 10.3390/foods9111663
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effects of Flaxseed Sources on the Egg ALA Deposition and Hepatic Gene Expression in Hy-Line Brown Hens

Abstract: Healthy diets are necessary for both humans and animals, including poultry. These diets contain various nutrients for maintenance and production in laying hens. Therefore, research was undertaken to explore the efficiency of various dietary flaxseed sources on the n-3 deposition in the egg yolk and gene expression in laying hens. Five dietary groups were analyzed, i.e., (i) a corn-based diet with no flaxseed (FS) as a negative control (NC), (ii) a wheat-based diet supplemented with 10% whole FS without multi-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 44 publications
4
8
0
1
Order By: Relevance
“…Petrovic et al (2012) and Schumann et al (2000) showed that diets containing 2% and 4% of flaxseed oil, respectively, reduced egg production in laying eggs. Shahid et al (2020), consistently with our results, pointed out a decrease in egg mass in hens fed with a long-term (12 weeks) flaxseed oil-containing diet. It was previously stated that flaxseed diets adversely affected egg production by impairing the feed digestibility due to the anti-nutritional factors in flaxseed (Ahmad, 2017).…”
Section: Discussionsupporting
confidence: 93%
“…Petrovic et al (2012) and Schumann et al (2000) showed that diets containing 2% and 4% of flaxseed oil, respectively, reduced egg production in laying eggs. Shahid et al (2020), consistently with our results, pointed out a decrease in egg mass in hens fed with a long-term (12 weeks) flaxseed oil-containing diet. It was previously stated that flaxseed diets adversely affected egg production by impairing the feed digestibility due to the anti-nutritional factors in flaxseed (Ahmad, 2017).…”
Section: Discussionsupporting
confidence: 93%
“…However, there have been some negative reports that the use of fish oil for egg production can lead to the development of a fishy taste ( Gonzalez-Esquerra and Leeson, 2000 ), and the high fiber content of linseed and its antinutritional components, such as cyanogenic glycosides, phytic acid and mucilage, can also negatively affect nutrient absorption ( Bean and Leeson, 2003 ). The use of linseed oil instead of linseed is effective in reducing the fiber content and facilitating the absorption of eggs ( Shahid et al, 2020 ). The results of this study showed that the addition of 2.5% linseed oil was effective in enriching eggs with n-3 fatty acids without affecting egg quality.…”
Section: Discussionmentioning
confidence: 99%
“…The room temperature was maintained between 22 and 26℃, and light exposure was controlled with a light/dark cycle of 16:8 h. Illumination was provided by incandescent lamps with an intensity of 10 lx (at bird-head level). After the initial 4 wk, refer to the dosage added in previous studies, nutritional additives were supplemented to the diet as follows: CON—control diet, LO—supplemented with 25 g of linseed oil/kg feed ( Shahid et al, 2020 ). ME–supplemented 2 g of marigold extract/kg feed ( Grčević et al, 2019 ), and SY–supplemented 0.2 g of selenium yeast/kg feed ( Han et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…Для увеличения энергии рациона обычно практикуется добавление масла и жира. В ряде исследований предлагается использовать жирные кислоты в рационе для увеличения энергии [5][6][7][8][9][10][11]. Очень мало исследований касалось использования сахарозы в кормах [12][13][14][15][16][17][18][19], хотя NRC предлагал вариант рациона птицы с использованием до 15% чистой сахарозы в 1984 году.…”
Section: введение / Introductionunclassified